2012
DOI: 10.1074/jbc.m111.307579
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Heat Shock Protein 70 Reduces T Cell Responses and Stimulatory Capacity of Monocyte-derived Dendritic Cells

Abstract: Background: An increased presence of Hsp70 has been observed in many clinical conditions; however, its role remains elusive. Results: Hsp70 reduces the stimulatory capacity of dendritic cells and T cell responses in an in vitro experimental setup. Conclusion: Hsp70 might moderate inflammatory reactions mediated by the immune system. Significance: Provides additional insight into the role of Hsp70 in autoimmune diseases, transplantation, and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…32 It is worth noting that the absence of minute amounts of contaminating endotoxin is mandatory to reveal the inherent suppressive functions of these HSPs, as nicely demonstrated by Stocki. 33,34 This very low level of contamination could account for the maturation effect of recombinant HSP110 on dendritic cells observed by Manjili et al 35 . In our setting, we eliminated this caveat as we used an HSP110 naturally present in the supernatant of CRC cell lines, and when we used purified HSP110, it was produced in a eukaryotic setting with no traces of LPS.…”
Section: E1170264-6mentioning
confidence: 98%
“…32 It is worth noting that the absence of minute amounts of contaminating endotoxin is mandatory to reveal the inherent suppressive functions of these HSPs, as nicely demonstrated by Stocki. 33,34 This very low level of contamination could account for the maturation effect of recombinant HSP110 on dendritic cells observed by Manjili et al 35 . In our setting, we eliminated this caveat as we used an HSP110 naturally present in the supernatant of CRC cell lines, and when we used purified HSP110, it was produced in a eukaryotic setting with no traces of LPS.…”
Section: E1170264-6mentioning
confidence: 98%
“…For example, it has been reported as a carrier of antigens to antigen-presenting cells (Lussow et al 1991;Nishikawa et al 2007), as pro-inflammatory mediator (Kono and Rock 2008), or on the contrary, as an anti-inflammatory molecule that inhibits maturation and induces the secretion of IL-10 in DCs (Detanico et al 2004;Motta et al 2007). However, the idea of HSP70 as a pro-inflammatory mediator has been considered controversial since several groups have shown that bacterial products often present in HSP70 protein preparations were responsible for the detected pro-inflammatory phenotype (Bausinger et al 2002;Bendz et al 2008;Stocki et al 2012). Therefore, for the experiments performed here, HSP70 preparation with less than 2.1 EU LPS/mg was used.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy surrounds many HSPs and their proinflammatory roles, and mainly results from endotoxin contamination artefacts which seems to be commonly overlooked due to a dogmatic approach adopted by some of the scientific community. Many reviews were written and argued for or against mammalian HSP70 proinflammatory functions; however the fact remains that in those publications where the striking “danger signal-like” proinflammatory activity of HSP70 was shown, researchers used the endotoxin contaminated recombinant protein provided by Stressgen Biotechnologies [16, 25, 26]. Therefore in this paper we dismiss any data from studies where HSP70 endotoxin contamination was neglected and we will concentrate only on reports where HSP70 purified from a nonbacterial origin was used or studies where endotoxin contamination was stringently controlled.…”
Section: Tantrum About Proinflammatory Functions Of Hsp70mentioning
confidence: 99%